Verifying the attenuation of earplugs in situ : Method validation on human subjects including individualized numerical simulations - Bockstael, Annelies; Van Renterghem, Timothy; Botteldooren, Dick; D'Haenens, Wendy; Keppler, Hannah; Maes, Leen; Philips, Birgit; Swinnen, Freya; Vinck, Bart (The Journal of the Acoustical Society of America, 2009)
The microphone in real ear (MIRE) protocol allows the assessment of hearing protector's (HPD) attenuation in situ by measuring the difference between the sound pressure outside and inside the ear canal behind the HPD. Custom-made earplugs have been designed with an inner bore to insert the MIRE probe containing two microphones, the reference microphone measuring the sound pressure outside and the measurement microphone registering the sound pressure behind the HPD. Previous research on a head and torso simulator reveals a distinct difference, henceforth called transfer function, between the sound pressure at the MIRE measurement microphone and the sound pressure of interest at the eardrum. In the current study, similar measurements are carried out on humans with an extra microphone to measure the sound pressure at the eardrum. The resulting transfer functions confirm the global frequency dependency found earlier, but also show substantial variability between the ears with respect to the exact frequency and amplitude of the transfer functions' extrema. In addition, finite-difference time-domain numerical models of an ear canal with earplug are developed for each individual ear by including its specific geometrical parameters. This approach leads to a good resemblance between the simulations and their corresponding measurements.